Strategi Pengembangan Klaster Usaha Mikro Kecil dan Menengah Keripik Tempe di Sanan Malang - Ferdinand, Ferdinand (Jurnal Aplikasi Manajemen, 2016)
This study was conducted to see more about the MSME Cluster of Tempe Chips in Sanan Malang. The method uses descriptive qualitative to describe more detail about MSME Cluster of Tempe Chips. The survey results reveal that MSME Cluster of Tempe Chips in Sanan is an active cluster. There are internal and external obstacles in the development of the cluster and the authors recommend development strategies as follows: 1) establish community entrepreneurs tempe chips; 2) the development of business scale; 3) increase the governmental support.